Notes on Destructive Insects of Ghont in Damoh, Madhya Pradesh - Gokulpure, R. S.; Maurya, R. C.; Mehra, B. P. (Indian Forester, 1970)
The authors record fifteen insect species which were found causing damage to ghont (Zizyphus xylopyra), an important plant species, in its natural environs in Damoh, Madhya Pradesh. The parasites of these insects, reared in the laboratory, have also been recorded. Biological notes on each insect species have also been given under each in the text. Mathur and Singh (1960) record 14 insect species on ghont.